GRAMMATICAL ERRORS MADE BY GRADE 10 LEARNERS WHEN WRITING ENGLISH DESCRIPTIVE ESSAYS - Ramaoka, Sekgalabje Isaiah; Chauke, Titos (Universitas Islam Sumatera Utara (UISU), 2024)
The aim of the study was to investigate grammatical errors made by learners when writing descriptive essays. 57 Grade 10 learners were purposively sampled to participate in the study. A preliminary assessment was conducted to inform the researchers’ selection criteria, and to ensure the selection of an information-rich learner sample that possessed participant qualities methodologically sought after by the researchers. The study adopted a qualitative research approach to allow the researchers to investigate the learners’ grammatical errors through a strategic administering of a descriptive essay writing task to elicit qualitative data from the sampled study participants. The sampled high school served as the case study site where an in-depth investigation of the grammatical errors made by Grade 10 learners when writing descriptive essays was carried out. To collect data from the 57 sampled learners, a descriptive essay writing task was administered, whereby learners were required to write an essay of 500 words under invigilated classroom conditions. Corder’s Error Analysis model and Ellis’s Procedural Analysis were jointly applied to analyse the collected data. Results of the study revealed that the participants committed grammatical errors that were categorised as sentence fragments, verb tense errors, concord errors, the use of contractions, sentence-initial conjunction, and inappropriate use of personal pronouns. These errors were mainly attributed to the influence of both the learners’ Sepedi home language and also their activity on social media platforms.